Integrated Reporting and Investment: How are They Related? - Martanti, Bernadeta Susilo; Hermanto, Dessy Astuti; Noviyanti, Elin; Andriany, Windy Rizkika (Journal the Winners: Economics, Business, Management, and Information System Journal, 2020)
The research aimed to explore how integrated reporting potentially impact the investor decision within mandatory and voluntary regulation. The method used was exploration of arguments from several researchers, either from theoretical and empirical basis, or literature review. The method of this qualitative research was dividing the literature into categories which in this research would be mandatory and voluntary regulations. The sub categories were divided by two countries which were Africa and The United States as research objects. The result and discussion were integrated reporting increases the value relevance of information produced by the company and underline the way companies create a value over the short until long term by informing business model, corporate strategy, and forecasting view. The result shows that Integrated Reporting will be more useful if the Government mandates the regulation like in Africa. It is considered that when Integrated Reporting potentially impacts the investors’ decision assured by professional services, these disclosures will be more accurate and reliable. A contribution for the government to create a clear regulation of the integrated report and provide an assurance service to assure the accuracy of information in the Integrated Report will be our expectation.